Azo dye decolorization by a halotolerant consortium under microaerophilic conditions. (April 2020) - Guo, Guang; Li, Xiaohua; Tian, Fang; Liu, Tingfeng; Yang, Feng; Ding, Keqiang; Liu, Chong; Chen, Jiasheng; Wang, Chongyang
Abstract: As a result of the use of a large amount of salt in dye industries, azo dye decolorization is often needed under hypersaline environments and low dissolved oxygen. Consortium GG-1, which is able to decolorize azo dyes in high salt concentrations and microaerophilic conditions, can be enriched using Metanil Yellow. Consortium GG-1 is mainly composed of Zobellella (62.25%), Rheinheimera (12.4%) and Marinobacterium (9.44%) and is able to decolorize azo dyes under 1%–10% salinity. The activities of azoreductase, laccase and lignin peroxidase were also measured. Together with the detected intermediates and the results obtained from FTIR, the decolorization process of Metanil Yellow was proposed. The influences of pH, initial concentration of azo dyes and concentration of yeast extract on the decolorization rate were also detected. Meanwhile, consortium GG-1 was identified with wide substrate specificity to dyes such as Direct Blue B, Acid Black ATT, and Acid Violet 7. Therefore, consortium GG-1 was identified with potential use in azo dye elimination. Highlights: Consortium GG-1 is able to decolorize azo dye under a wide range of salinity. GG-1 shows best efficiency of decolorization under saline and microaerophilic conditions. FTIR, GC-MS and enzyme analysis are used to study decolorization mechanism. Environmental factors influencing the decolorization rate are discussed. GG-1 is identified with high salt tolerance, wide pH and substrate range.